ASSESSMENT OF INTEGRATION EFFECTS IN THE EURASIAN - al-Hoderi, M. (Farabi Journal of Social Sciences, 2020)
This article considers the strategic directions of economic development of the member states of the Eurasian Economic Union, based on available resources and objective opportunities for their joint effective use. With all the turbulence and uncertainty that exist today in the world economy, the definition of the main directions for the coordination of economic policies looks extremely important and timely. In general, by 2030, the results of the economic development of the EAEU have to show the world competitiveness of the integration association.In spite of the fact that this idea hasn’t been understood and underestimated by most of politicians of that time in the CIS, today became relevant and widely demanded not only in a business community, but also at the public and humanitarian level. Integration processes in the Eurasian space are increasingly gaining momentum. Moreover, many joint platforms that strengthen Eurasian integration are already functioning actively and successfully: Eurasian Development Bank, Eurasian Economic Club of Scientists, Eurasian Business Council, Eurasian Media Forum, Eurasian Association of Universities and many others. International practice shows that any interstate association is experiencing different stages in its development and is complemented by new forms of cooperation. In the conditions of the modern economic reality which is characterized by tendencies of globalization and regionalization, member states of EAEU have taken the path of uniting the potentials of national economies for their sustainable development.